‘Absent and yet Somehow Present’: Idealized Landscapes and the Counter-historical Impulse in Contemporary Northern Irish Photography and Writing - Stephanie Lehner (Review of Irish Studies in Europe)
This article explores how three artists are responding to the idealized landscape that is contemporary Northern Ireland. I argue that the rural/urban dichotomy which implicitly or explicitly forms a point of departure in the photographic collections of David Farrell’s Innocent Landscapes (2001) and John Duncan’s Trees from Germany (2003) is also evident in David Park’s 2008 novel, The Truth Commissioner, offering a new lens to explore the play of absences and presences that constitute the peace process. The three works allow us to perceive how idealized landscapes act as façades that conceal, contain and defer alternative realities.